2021
DOI: 10.3389/fonc.2021.644303
|View full text |Cite
|
Sign up to set email alerts
|

From Good to Bad: The Opposing Effects of PTHrP on Tumor Growth, Dormancy, and Metastasis Throughout Cancer Progression

Abstract: Parathyroid hormone related protein (PTHrP) is a multifaceted protein with several biologically active domains that regulate its many roles in normal physiology and human disease. PTHrP causes humoral hypercalcemia of malignancy (HHM) through its endocrine actions and tumor-induced bone destruction through its paracrine actions. PTHrP has more recently been investigated as a regulator of tumor dormancy owing to its roles in regulating tumor cell proliferation, apoptosis, and survival through autocrine/paracrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 173 publications
(222 reference statements)
0
17
0
Order By: Relevance
“…PTHrP has been reported to display complex and sometimes opposite actions toward cancer and its actions likely depend on tumor type, stage, and metastatic microenvironment. Nevertheless, most preclinical data support a pro-tumorigenic role for PTHrP, (38) and the present study illustrates a mechanistic link between PTHrP expression and EMT-driven CSC phenotype in TNBC tumor cells (seed) as well as bone marrow (soil). We demonstrate here that anti-PTHrP mAb treatment reverses EMT and has efficacy against established TNBC-derived skeletal lesions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…PTHrP has been reported to display complex and sometimes opposite actions toward cancer and its actions likely depend on tumor type, stage, and metastatic microenvironment. Nevertheless, most preclinical data support a pro-tumorigenic role for PTHrP, (38) and the present study illustrates a mechanistic link between PTHrP expression and EMT-driven CSC phenotype in TNBC tumor cells (seed) as well as bone marrow (soil). We demonstrate here that anti-PTHrP mAb treatment reverses EMT and has efficacy against established TNBC-derived skeletal lesions.…”
Section: Discussionmentioning
confidence: 56%
“…( 38 ) For example, PTHrP expression in breast cancer patients has been linked to improved outcomes in a prospective patient cohort, ( 39 ) and the ablation of PTHrP has been reported to increase tumor progression and inhibit animal survival in the MMTV‐neu mouse, ( 40 ) a late‐onset mammary cancer model. However, most preclinical data support a pro‐tumorigenic role for PTHrP ( 38 ) ; we recently examined tissue specimens from a cohort of treatment‐naive women newly diagnosed with TNBC and assessed that tumor cores from the majority of patients displayed very high PTHrP expression compared with normal breast samples. We found that PTHrP was a statistically significant independent prognostic factor for central nervous system progression‐free survival and for overall survival in TNBC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms can be responsible for hypercalcemia in malignancy, including parathyroid hormone-related peptide and osteolytic metastases-related hypercalcemia [10]. It's well known, in fact, that Parathyroid Hormone-related Protein (PTHrP) can be responsible for humoral hypercalcemia of malignancies (HHM) through endocrine action and tumor-induced bone destruction [11]. It must be also added that, in our patient, the multi-parametric evaluation of patient (clinical symptoms, physical examination, EKG, echocardiography, chest x-ray, CT scan and laboratory findings) were useful to suspect and recognize the pulmonary malignancy and its left atrial extension [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…PTHrP intervenes in the physiological regulation of bone remodeling. It is produced locally (paracrine function) by the progenitors of osteoblasts; acts by promoting the differentiation of mature osteoblasts by inhibiting the apoptosis process that allows bone formation; it also stimulates the differentiation of osteoclasts responsible for bone resorption instead [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is an indispensable hormone for the evolution of pregnancy and for fetal development [ 3 ]. Unlike PTH, it acts in many tissues as a paracrine or autocrine factor rather than a classical hormone [ 3 , 10 ]. In the kidney, PTHrP is abundantly expressed and upregulated, showing growth-modulatory and pro-inflammatory properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%